“Language Planning in Zimbabwe; the Conservation and Management of Indigenous Languages in Zimbabwe”. Paper presented at ICOMOS 14th General Assembly and Scientific Symposium at Victoria Falls, Zimbabwe on the 30th of October 2003. - Viriri, Advice (ICOMOS, 2016)
It is necessary to promote and enhance African languages as intangible cultural heritage. This heritage needs conservation and management in the form of language planning and policy making that would contribute towards the restoration of the indigenous speakers’ humanity, identity and culture. Our indigenous languages seek to focus on African philosophy, aesthetics, art, performing arts, politics, sociology, sport and other subjects. These languages would explore ways in which the forms of African cultural life and expression will help to shape, inform and influence cultures and intellectual traditions across the globe. It is necessary to transcend colonial alienation as “part and parcel of the anti-imperialist struggles of [Zimbabweans] and African peoples” whose indigenous languages “were associated with negative qualities of backwardness, underdevelopment, humiliation and punishment.” (Ngugi, 1981:28). This paper will testify the superiority of our indigenous languages to English. The researcher believes in the maxim “free your mind”: the mind must be liberated even from the confines of biased Afro-centric thought. These languages will convey the profound need for the Zimbabwean people to be re-located historically, economically, socially, linguistically, politically, and philosophically. For a number of years, Africans have been devoid of their cultural, economic, religious, political and social heritage. They have been living on the periphery of Europe. It is this “illusion of the fringes” that this paper seeks to eliminate and restore “the African person as an agent in human history…” (Asante, 2003:1)This will answer questions on how African cultural and intellectual traditions radically and indelibly shape the world. In demanding to know the total system of truth about the world, the first step is to know the reality of our own existence through our indigenous languages.